2009
DOI: 10.1002/ceat.200900092
|View full text |Cite
|
Sign up to set email alerts
|

Fluidization Characteristics in Micro‐Fluidized Beds of Various Inner Diameters

Abstract: The fluidization characteristics of quartz sand and fluid catalytic crack (FCC) catalyst particles in six micro-fluidized beds with inner diameters of 4. 3, 5.5, 10.5, 15.5, 20.5, and 25.5 mm were investigated. The effects of bed diameter (D t ), static bed height (H s ), particles and gas properties on the pressure drop and minimum fluidization velocity (u mf ) were examined. The results show that the theoretical pressure drops of micro-fluidized beds deviated from the experimental values under different par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…This value is very close to that previously found in the 5‐cm stainless‐steel FBCVD reactor using pure argon 21. According to Liu et al 22 and to Guo et al 23, when the reduction of the reactor diameter leads to modifications of the FB hydrodynamics, the U mf value increases and a pressure overshoot appears on the pressure drop curves, due to wall effects. In our case, it can then be concluded that the FB hydrodynamics is not markedly modified by the reactor diameter reduction.…”
Section: Resultssupporting
confidence: 89%
“…This value is very close to that previously found in the 5‐cm stainless‐steel FBCVD reactor using pure argon 21. According to Liu et al 22 and to Guo et al 23, when the reduction of the reactor diameter leads to modifications of the FB hydrodynamics, the U mf value increases and a pressure overshoot appears on the pressure drop curves, due to wall effects. In our case, it can then be concluded that the FB hydrodynamics is not markedly modified by the reactor diameter reduction.…”
Section: Resultssupporting
confidence: 89%
“…In the literature, the impact of reducing the reactor diameter on gassolid fluidized bed hydrodynamics has only been studied for powders belonging to Geldart's groups A and B [5], which are easily fluidizable [6][7][8][9][10][11][12][13]. To the best of our knowledge, all studies have been performed at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In macroscale three‐phase fluidized beds, the static bed height scarcely affects U Lmf , which can be seen from many formulas for predicting U Lmf . However, the static bed height exerts a greater influence on the minimum fluidization velocity for the liquid‐solid or gas ‐solid systems at a smaller bed diameter . Figure shows the effect of the static bed height on U Lmf for gas‐liquid‐solid MFB with bed diameter of 10 mm of 740 μm solid particles.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al also observed the enhancement of U mf of 53 μm FCC particles in gas‐solid fluidized beds with bed sizes ranging from 0.7 mm to 5 mm. Guo et al investigated the fluidization behaviors in gas‐solid fluidized beds with six different inner diameters, and the results showed that the conventional Ergun equation underestimated U mf . They proposed a new empirical equation containing particle diameter and bed height.…”
Section: Introductionmentioning
confidence: 99%